Job turnover intention, social support and fear of COVID-19 among frontline nurses in hospital setting: An exploratory survey - Manisha Mehra; Nidhin Vasu; Poonam Joshi; Surya Kant Tiwari (Elsevier, 2024)
Background: With the emergence of the COVID-19 pandemic, the role of nurses came into the limelight. Despite efforts, concerns have grown about the nurse's support, interest in carrying out their job responsibilities, and fear of getting COVID-19 infection. Therefore, we aim to assess the prevalence and predictors of job turnover intention, social support, and fear of COVID-19 (FCV-19) among frontline nurses. Methods: A descriptive cross-sectional survey was conducted in May-June 2022, involving 229 nurses using total enumeration sampling technique. Standardized tools consisting of turnover intention scale, multidimensional scale of perceived social support, and FCV-19 scale were administered. The data was analyzed using IBM SPSS version 20.0. Descriptive and inferential statistics included the Kolmogorov-Smirnov test, Mann-Whitney U, and Kruskal-Wallis H test. Multiple linear regression analysis was performed to predict factors affecting the main variables. Results: The mean age of the study participants was 27.10 ± 2.72 years, with the majority being females (86.0 %). The results indicated that a significant proportion of nurses had the intention to leave the nursing profession (43.7 %). Majority of the nurses reported high social support (55.9 %) and low fear of COVID-19 (61.6 %). Regression analysis identified marital status and fear of COVID-19 as significant factors influencing job turnover intention. Conclusion: Our study suggested that approximately half of the nurses might leave nursing profession in the near future, even though they report high social support and low FCV-19, potentially have adverse effects on patient care within the hospital setting, necessitating urgent interventions from both nurse managers and hospital administrators.